Nutritional interventions for improving the endurance performance in athletes. (4th July 2022) - Ravindra, P. V.; Janhavi, P.; Divyashree, S.; Muthukumar, S. P.
Abstract: Endurance refers to the ability of skeletal muscles to perform continuously withstanding the hardships of exercise. Endurance exercises have three phases: pre-, during-, and post-workout phase. The nutritional requirements that drive these phases vary on intensity, type of workout, individual's body composition, training, weather conditions, etc. Generally, the pre-workout phase requires glycogen synthesis and spare glycogen breakdown. While workout phase, requires rapid absorption of exogenous glucose, insulin release to transport glucose into muscle cells, replenish the loss of electrolytes, promote fluid retention, etc. However, post-workout phase requires quick amino acid absorption, muscle protein synthesis, repair of damaged muscle fibres and tendon, ameliorate inflammation, oxidative stress, etc. Therefore, nutritional sources that can help these metabolic requirements is recommended. In this review, various dietary interventions including timing and amount of nutrient consumption that can promote the above metabolic requirements that in turn support in improving the endurance potential in athletes are discussed. HIGHLIGHTS: Review article describes nutritional requirements of endurance exercises. It also describes nutritional interventions to enhance the endurance potential in athletes.